2015
DOI: 10.2217/whe.15.46
|View full text |Cite
|
Sign up to set email alerts
|

Serum Markers for the Noninvasive Diagnosis of Endometriosis

Abstract: Endometriosis is a disease that affects millions of women worldwide and its diagnosis is still challenging. Medical history, symptoms together with imaging data may address the correct diagnosis, but the gold standard remains laparoscopic assessment with histological confirmation. The development of serum markers as diagnostic tools for endometriosis may allow a prompt and noninvasive diagnosis. Several serum biomarkers have been investigated over the years, but none of these have shown a clinical utility and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…Proteomic approaches have been used to identify possible biomarkers correlating with endometriosis pathology, mostly in serum or PF 2,28,29 . Besides critical cytokines and growth factors such as interleukin IL-1β, IL-6, IL-10 or VEGF, these studies have also identified alterations in indicators of oxidative stress, such as paraoxonase, superoxide dismutase (SOD), thioredoxin binding protein, and others 30 , again lending support to the hypothesis of oxidative stress as a hallmark of disease.…”
mentioning
confidence: 99%
“…Proteomic approaches have been used to identify possible biomarkers correlating with endometriosis pathology, mostly in serum or PF 2,28,29 . Besides critical cytokines and growth factors such as interleukin IL-1β, IL-6, IL-10 or VEGF, these studies have also identified alterations in indicators of oxidative stress, such as paraoxonase, superoxide dismutase (SOD), thioredoxin binding protein, and others 30 , again lending support to the hypothesis of oxidative stress as a hallmark of disease.…”
mentioning
confidence: 99%
“…This is a behavioral parameter that has not been replicated from the clinical scenario because women with endometriosis tend to show a higher incidence of introversion anxiety. 48 This indicates that the behavioral tests used in this study might not be sensitive enough to measure certain aspects of anxiety that can be present in the animal, since our previous work has demonstrated that administered external stress can produce increased anxiety as assessed by increased fecal pellet counts. 11 Our data parallel the clinical observations found in women with endometriosis, 13,14 showing a decrease in cortisol basal state, even when controlling for treatment status of the patients.…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, elevated monocyte chemotactic protein-1 (MCP-1) values were observed in peritoneal fluid and plasma in women with endometriosis, especially in the early stages of the disease. Another study revealed its elevated values in the more advanced stages [8].…”
Section: Immunological Markersmentioning
confidence: 94%
“…It is considered that the development of non-invasive diagnostic tests such as 'biomarkers' would have a clear impact in reducing diagnosis time and monitoring the progress of the disease and the effectiveness of treatment [5]. To replace invasive diagnostic methods, biomarkers could be considering clinically useful if they comply with predetermined criteria -sensitivity 94% and specificity 79% [8,9]. This paper aims to describe and discuss the current status of biomarkers of endometriosis in serum.…”
Section: Introductionmentioning
confidence: 99%